EAM conditioning regimen followed by autologous hematopoietic Stem Cell Transplantation for relapsed, refractory and high risk lymphomas - Mohamed BEKADJA; Tamim ALSULIMAN; Rachid BOUHASS; Abdessamed ARABI; Mohamed BRAHIMI; Soufi OSMANI; Nabil YAFOUR; Souad TALHI (Mediterranean Journal of Hematology and Infectious Diseases)
Hematopoietic Stem Cell Transplant is the  standard  treatment of refractory / recurrent lymphomas, most of conditioning regimens in this cases are BCNU-based as for BEAM & CBV , this agent (BCNU) is well-known for its severe lung toxicity . In our department we tried to assess effectivity and safety of approaches that contain BCNU-free conditioning regimen as for this EAM protocol in Autologous Stem Cell Transplant.